Genetic variability analysis among clinical Candida spp. isolates using random amplified polymorphic DNA - Pinto, Patrícia M; Resende, Maria A; Koga-Ito, Cristiane Y [UNESP]; Tendler, Miriam (Instituto Oswaldo Cruz, Ministério da Saúde, 2004)
The patterns of genetic variation of samples of Candida spp. isolated from patients infected with human immunodeficiency virus in Vitória, state of Espírito Santo, Brazil, were examined. Thirty-seven strains were isolated from different anatomical sites obtained from different infection episodes of 11 patients infected with the human immunodeficiency virus (HIV). These samples were subjected to randomly amplified polymorphic DNA (RAPD) analysis using 9 different primers. Reproducible and complex DNA banding patterns were obtained. The experiments indicated evidence of dynamic process of yeast colonization in HIV-infected patients, and also that certain primers are efficient in the identification of species of the Candida genus. Thus, we conclude that RAPD analysis may be useful in providing genotypic characters for Candida species typing in epidemiological investigations, and also for the rapid identification of pathogenic fungi.
Keywords: polymerase chain reaction; random amplified polymorphic DNA; candidosis; Candida spp